2018
DOI: 10.1093/milmed/usy194
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin Allergy…Maybe Not? The Military Relevance for Penicillin Testing and De-labeling

Abstract: A penicillin allergy label is a risk to military readiness secondary to associated increases in the length of hospitalizations and emergency department and medical visits. Penicillin de-labeling is a simple intervention that can improve readiness, significantly decrease health care costs and prevent antibiotic resistance, as well as antibiotic-associated adverse events. The military allergist should be "front and center" providing expertise guidance and leadership for clinic and hospital-based penicillin de-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…24 When these potential savings are applied to the military insurance population of 9.4 million beneficiaries (TRICARE, including active duty, their dependents, and all retirees participating in the program), the results showed that this could impart a savings of nearly $1.7 billion annually, using the model by Macy and Contreras. 23,25,26 Previously with colleagues, I reviewed penicillin's role in military history, compiled data from relevant studies from military penicillin allergy rates and delabeling efforts, and calculated the potential economic impact of penicillin allergies along with the benefits of testing. 26 Calculations were estimated using the TRICARE beneficiary population (9.4 million) × the estimated prevalence (10%) to get an estimate of 940,000 TRICARE patients with penicillin allergy in their medical record.…”
Section: Cost Of Penicillin Allergiesmentioning
confidence: 99%
See 4 more Smart Citations
“…24 When these potential savings are applied to the military insurance population of 9.4 million beneficiaries (TRICARE, including active duty, their dependents, and all retirees participating in the program), the results showed that this could impart a savings of nearly $1.7 billion annually, using the model by Macy and Contreras. 23,25,26 Previously with colleagues, I reviewed penicillin's role in military history, compiled data from relevant studies from military penicillin allergy rates and delabeling efforts, and calculated the potential economic impact of penicillin allergies along with the benefits of testing. 26 Calculations were estimated using the TRICARE beneficiary population (9.4 million) × the estimated prevalence (10%) to get an estimate of 940,000 TRICARE patients with penicillin allergy in their medical record.…”
Section: Cost Of Penicillin Allergiesmentioning
confidence: 99%
“…23,25,26 Previously with colleagues, I reviewed penicillin's role in military history, compiled data from relevant studies from military penicillin allergy rates and delabeling efforts, and calculated the potential economic impact of penicillin allergies along with the benefits of testing. 26 Calculations were estimated using the TRICARE beneficiary population (9.4 million) × the estimated prevalence (10%) to get an estimate of 940,000 TRICARE patients with penicillin allergy in their medical record. 25 If 90% of those patients were delabeled, this would equal 846,000 TRICARE patients.…”
Section: Cost Of Penicillin Allergiesmentioning
confidence: 99%
See 3 more Smart Citations